EXISTENTIAL PROBLEMS EXPERIENCED IN OLD AGE: CAUSES AND SOLUTIONS - Bogdanova, Natalija (Socialinė teorija, empirija, politika ir praktika, 2007)
The main goal of article is to dispute a question on the causes of existential problems experienced in old age. There is a wide range of cases when old people suffer from inner emptiness or dissatisfaction of passed years. The sense of meaningful life can be lost for the reason of some physical troubles that occur in old age as well as psychological problems caused by both social and inner factors. Humanistic-existential approach interprets these questions due to the lack of the meaning of life. Supposedly, old aged persons would restore the meaning of their life with the help of liked labour, fraught with respect intercommunion as well as belief in God. The research presented after the theory part shows the view of social work students of old people personalities. Commonly, respondents demonstrated kindly view on old aged people. However this view can be treated as unconsidered and superficial. Students did not welcome possible work with old people. On the other hand, students agreed that old people have a great potential to self-actualization that in fact is a chance to search and to restore the meaning of life in old age. Contradictions in students' view expose that the subject of existential problems experienced in old age is studied insufficient and needs intense research.
Keywords: Old age; Existential problems; Humanistic-existential approach; Social work students